Cell type- and region-specific enhancement of adult hippocampal neurogenesis by daidzein in middle-aged female mice. (December 2016) - Yamada, Jun; Hatabe, Jun; Tankyo, Kaori; Jinno, Shozo
Abstract: Adult hippocampal neurogenesis is associated with various brain functions, such as learning, memory, and emotion. Intriguingly, reduction in new cell production in the hippocampus in middle age may underlie some of the cognitive deficits. Among several factors that may affect adult hippocampal neurogenesis, estrogens have been suggested to be critically involved in the cognitive impairment of postmenopausal women. Phytoestrogens, such as daidzein and genistein, are expected to work as estrogen substitutes. In this study, we aimed to clarify the effects of daidzein on adult hippocampal neurogenesis using middle-aged (12-month-old) female mice. Animals received daily intraperitoneal injections of daidzein or vehicle for four weeks, and the cells at specific stages of neurogenesis were presumptively defined using molecular markers. Administration of daidzein did not affect the numerical densities (NDs) of primary progenitors, early transient amplifying progenitors (TAPs), and astrocytes. In contrast, the NDs of late TAPs, neural progenitors, and immature granule cells were increased by daidzein. The NDs of proliferating cells, but not apoptotic cells, were also increased by daidzein. To examine the effects of daidzein on maturation of adult-born cells, we three-dimensionally traced their dendritic arbors: the branch number, total length, and intersection number (Sholl analysis) of immature granule cells were increased by daidzein. In general, the effects of daidzein were more dominant in the dorsal region than in the ventral region. The cell type- and region-specific enhancement of adult hippocampal neurogenesis by daidzein provides a key to understanding the actions of estrogen substitutes for the treatment of postmenopausal women. Highlights: Daidzein promotes the hippocampal neurogenesis in middle-aged female mice. Progenitors at early stages of neurogenesis are not affected by daidzein. Neural progenitors and immature granule cells are increased by daidzein. Proliferating cells, but not apoptotic cells, are also increased by daidzein. Effects of daidzein are more dominant in the dorsal than in the ventral hippocampus.